“Manusia Silver” As a Symbol of Marginality: Analysis of Social Semiotical in The Channel YouTube of Vice Indonesia - Ibrahim, Azhar; R. Myrna Nur Sakinah (Morphosis: Journal of Literature, 2025)
This research analyzed how “manusia silver” is represented as a symbol of marginality using the social semiotic approach developed by M.A.K. Halliday. “Manusia silver” are portrayed as one of the most marginalized individuals in the video published by Vice Indonesia’s YouTube channel due to the harsh socio-economic conditions in the urban environment. Using social semiotic theory, this article explores how visual and linguistic practices constitute meanings of marginality in the video and consolidate a particular understanding of manusia silver’s social position. The analysis underlines the fact that the painted bodies in silver must serve not only as a source of livelihood but also symbolize resistance to the social system that forces them into such a degrading life. The results indicate that “manusia silver” has now become an ’iconic visual’ of social injustice, underlining the human tension between living an individual life and the oppressive structure of society.